New species of Anacanthorus (Dactylogyridae: Anacanthorinae) from the gills of Hoplerythrinus unitaeniatus and Erythrinus erythrinus (Characiformes: Erythrinidae) of the coastal drainage in the Eastern Amazon, Brazil - Neto, João F. Santos; Muriel-Cunha, Janice; Domingues, Marcus V. (Zootaxa, 2019)
Species of Anacanthorus are described from the gills of Hoplerythrinus unitaeniatus and Erythrinus erythrinus of drainage systems in the Northeastern Pará State, Brazil. Anacanthorus scyphophallus sp. n. has a male copulatory organ (MCO) with two small flaps in the distal portion; hooks with proximal shank dilatation comprising ½ of the shank length. Anacanthorus ataidei sp. n. has an elongated MCO, with ribbon-like ornaments; hooks without proximal shank dilatation. Anacanthorus siphonocommus sp. n. has an MCO with aculeiform ornaments in the distal portion; hooks with proximal dilatation in the shank comprising ½ of the shank length. Anacanthorus maratininguensis sp. n. has an MCO with a small projection in the form of a hook in the distal region; hooks with proximal dilatation comprising ½ of the shank length. Anacanthorus lacinimentulatus sp. n. has an MCO with extrovert flap skirting its distal region; shank of hooks with proximal dilatation comprising ½ of the total shank length. Anacanthorus cururutuiensis sp. n. presents an MCO with flexed lateral flap in the distal region; hooks with proximal dilatation in the shank comprising ¼ of the shank length. Anacanthorus circumspatulatus sp. n. has an MCO with ornaments in the form of pointed and interleaved blades; hooks with proximal shank dilatation comprising approximately ½ of the shank length. Anacanthorus acrophallus sp. n. has MCO with a small pointed sinistral flap; hooks with proximal dilatation in the shank comprising 1/3 of the shank length. The host-parasite diversity scenario and specificity of Anacanthorus species regarding their characiform hosts are also discussed in this study.